767. Incidence of C. difficile infection (CDI) Cases by CDI-Standardized Infection Ratio (SIR) Among Centers for Medicare and Medicaid Services (CMS)-Participating Short-Term Acute Care Hospitals (ACH) Post Implementation of the Hospital-Acquired Condition Reduction Program (HAC-RP). (4th December 2021) - Rodriguez, Mauricio; Chitra, Surya; Lavallee, Paige; Mallow, Peter J; Lodise, Thomas; Lodise, Thomas
Abstract: Background: The HAC-RP is a Medicare pay-for-performance program that links Medicare Part A payments to ACH healthcare quality. Starting in 2015, ACHs ranking in the lower 25% for HAC quality measures are subject to a 1% payment reduction. C. difficile infection (CDI) is 1 of 6 quality measures included in the HAC-RP. Hospitals with a CDI-SIR ≥ 1, indicating that observed yearly CDI cases exceed predicted CDI cases, are subject to a payment reduction, depending on their performance on other HAC quality measures. Little data are available on the CDI-SIR and observed CDI cases among CMS-participating ACH. Methods: The HAC hospital data were obtained from CMS (publicly available at https://data.cms.gov/ ). Definitive Healthcare imported the data using a Structured Query Language based program and linked the CMS data (October yearly reports) with key hospital-level variables in the Definitive Healthcare Data Platform. Data on CDI cases between 2015 - 2018 among CMS-participating short-term ACHs were obtain from Definitive Healthcare and stratified in quartiles by hospital discharges per year. Within each quartile, the number of observed CDI cases were compared descriptively among ACHs with a CDI-SIR ≥1 vs. < 1 by year. Results: Number of ACHs with a CDI-SIR ≥1 vs. < 1 within each hospital discharge quartile by year is displayed in Figure 1. The number of ACHs with CDI-SIR ≥1 increased in 2015, were maintained in 2016, declined in 2017 and again in 2018. Within each quartile, the average observed cases per year were higher for ACHs with CDI-SIR ≥ 1 (Figure 2). After 2015 total observed cases declined in ACHs with CDI-SIR ≥ 1 but remained unchanged in ACH with CDI-SIR < 1 (Figure 3). Figure 1. Number of ACH with CDI-SIR ≥1 vs. <1 Within Each Hospital Discharge Quartile Between 2015-2018 Figure 2. Average Number of and Total Observed Cases per ACH within Each Hospital Discharge Quartile by CDI-SIR ≥1 Figure 3. Total Observed Cases by CDI-SIR ≥ between 2015-2018 Conclusion: Observed cases were similar regardless of CDI-SIR score, although approximately 75% of ACHs had a CDI-SIR < 1. HAC-RP penalizes short-term ACHs with a CDI-SIR ≥1 and appears to be effective in reducing CDI cases. However, the observed increase of cases over the 4-year period among ACHs with CDI-SIR < 1 post HAC-RP implementation is concerning. Greater focus is needed to reduce CDI cases across all ACHs, irrespective of CDI-SIR given the burden of disease and associated morbidity and mortality. Disclosures: Mauricio Rodriguez, Jr., PharmD, BCPS, BCCCP, BCIDP, Paratek Pharmaceuticals, Inc. (Employee, Shareholder) Surya Chitra, PhD, Paratek Pharmaceuticals, Inc. (Consultant) Paige Lavallee, BA, Definitive Healthcare (Employee) Thomas Lodise, Jr., PharmD, PhD, Astra-Zeneca (Consultant)Bayer (Consultant)DoseMe (Consultant, Advisor or Review Panel member)ferring (Consultant)genentech (Consultant)GSK (Consultant)Melinta (Consultant)merck (Consultant, Independent Contractor)nabriva (Consultant)paratek (Consultant, Advisor or Review Panel member, Speaker's Bureau)shionogi (Consultant, Advisor or Review Panel member, Speaker's Bureau)Spero (Consultant)tetraphase (Consultant)Venatrox (Consultant) Thomas Lodise, Jr., PharmD, PhD, Melinta Therapeutics (Individual(s) Involved: Self): Consultant; Merck (Individual(s) Involved: Self): Consultant, Scientific Research Study Investigator; Paratek (Individual(s) Involved: Self): Consultant; Shionogi (Individual(s) Involved: Self): Consultant, Speakers' bureau; Spero (Individual(s) Involved: Self): Consultant; Tetraphase Pharmaceuticals Inc. (Individual(s) Involved: Self): Consultant